From eremitical to monastic settlements, from rural towards urban areas: the spatial evolution of the Portuguese eremitical congregation of São Paulo da Serra de Ossa - Volzone, R.; Fontes, J. L. (Architectures of the soul: Multidisciplinary approaches to the experiences and landscapes of seclusion and solitude, 2022)
The Portuguese Eremitical Congregation of São Paulo da Serra de Ossa was founded in 1482, combining a large number of eremitical settlements that had been documented since 1366, mainly in the Alentejo region (southern Portugal), under a centralised government. In 1578, an autonomous congregation was set up and became affiliated with the Hungarian Order of Saint Paul the First Hermit. This paper aims to analyse the impact of the transition from eremitical to monastic settlements, in terms of both settlement location and architectural typology. The 17 case studies presented in this paper have been identied in the geographical region in question. A census of the existing physical structures – sometimes scant remains only – was carried out through literature reviews, archival research and on-site morphological and spatial analyses, allowing for a critical interpretation to be gained of the monastic landscapes. This article shall serve to discuss the implications of the transition from the eremitical movement to the institutionalisation of the settlements, both in terms of their geography and spatial adaptations made as a result of these changes.